2019
DOI: 10.1186/s13018-019-1373-9
|View full text |Cite
|
Sign up to set email alerts
|

How to restore rotation center in total hip arthroplasty for developmental dysplasia of the hip by recognizing the pathomorphology of acetabulum and Harris fossa?

Abstract: PurposeTo restore rotation center exactly in total hip arthroplasty (THA) is technically challenging for patients with end-stage osteoarthritis due to developmental dysplasia of the hip (DDH). The technical difficulty is attributable to the complex acetabular changes. In this study, we investigated the pathomorphology of acetabulum and Harris fossa of Crowe types I to IV and discussed the method of restoring rotation center of the hip.MethodsThis study retrospectively reviewed 56 patients (59 hips) who underwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

6
2

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 16 publications
0
28
0
Order By: Relevance
“…Compared with the top part, the pathological changes at the bottom of the acetabulum that was relatively minor in hip revision cases, and the remnant of Harris fossa and acetabular notches could always been found. Zhang H et al [6] reported that the acetabular center was located on the average of 28 mm (range 25~31 mm, depending on the size of the acetabulum) above the vertical bisection of the anterior and posterior acetabular notches line, and the acetabular center was also at the cephalic side of the Harris fossa, near semilunar cartilage. The acetabular center could be located accurately in the hip revision surgery by this method.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with the top part, the pathological changes at the bottom of the acetabulum that was relatively minor in hip revision cases, and the remnant of Harris fossa and acetabular notches could always been found. Zhang H et al [6] reported that the acetabular center was located on the average of 28 mm (range 25~31 mm, depending on the size of the acetabulum) above the vertical bisection of the anterior and posterior acetabular notches line, and the acetabular center was also at the cephalic side of the Harris fossa, near semilunar cartilage. The acetabular center could be located accurately in the hip revision surgery by this method.…”
Section: Discussionmentioning
confidence: 99%
“…The remnant structures of the Harris fossa and acetabular notches on the bottom of the acetabulum were carefully exposed and identified. The acetabular center was located at a mean of 28 mm (range 25~31 mm, depending on the size of the acetabulum) above the perpendicular bisector of acetabular anterior and posterior notch line [5,6]. Sclerous acetabular bone bed was concentrically reamed using the above located point as the center of circles.…”
Section: Surgical Methodsmentioning
confidence: 99%
“…The Harris fossa was covered with osteophytes and restored its morphology by removing osteophytes (Fig.2B). The acetabular anterior and posterior notches were recognized and the perpendicular bisector of acetabular anterior and posterior notch line was marked.The acetabular center was loacted at 25 ~ 31 mm(mean 28.7 mm,depended on the size of the acetabulum) above the intersection point of the perpendicular bisector and acetabular anterior and posterior notch line (Fig.2C),which could also be located by ourself-developed acetabular center locator( Fig.2D) [7]. During the process of acetabular reaming, the anteversion was controlled in the range of 15°±10 °, while the inclination was 40°±10°, and the depth was to bottom of Harris fossa .…”
Section: Simulated Operation and Preoperative Planning For Restoring mentioning
confidence: 94%
“…The acetabular anterior and posterior notches were recognized and the perpendicular bisector of acetabular anterior and posterior notch line was marked. The acetabular center was loacted at 25 ~ 31 mm(mean 28.7 mm,depended on the size of the acetabulum) above the intersection point of the perpendicular bisector and acetabular anterior and posterior notch line [7] (Fig.4C).…”
Section: Surgical Techniquementioning
confidence: 99%
“…2C),which could also be located by ourself-developed acetabular center locator( Fig. 2D) [7]. During the process of acetabular reaming, the anteversion was controlled in the range of 15°±10 °, while the inclination was 40°±10°, and the depth was to bottom of Harris fossa.…”
Section: Simulated Operation and Preoperative Planning For Restoring mentioning
confidence: 96%